ответ:
решаем:
а) 2x + 3y = 16
3x - 2y = 11
из 1-го ур-ния y = (16 - 2x) / 3
подставляем во 2-е
3x - 2*(16 - 2x) / 3 = 11
9x - 32 + 4x = 33
13x = 65, x = 5, y = (16 - 2x) / 3 = 2
ответ: x = 5, y = 2
б) 6(x + y) = 5 - (2x + y)
3x - 2y = -3 (или -3 -3 = -6, уточни)
из 2-го у = (3х + 3) / 2
6(x + (3х + 3) / 2) = 5 - (2x + (3х + 3) / 2)
6(5x + 3) / 2 = 5 - (7x + 3) / 2
6(5x + 3) = 10 - (7x + 3)
30x + 18 = 10 - 7x - 3
37x = -11, x = -11/37, y = (3х + 3) / 2 = (-33+111) / (2*37) = 78 / (2*37) = 39/37
ответ: x = -11/37, y = 39/37
в) 2x + 3y = 3
5x - 4y = 19
y = (3 - 2x) / 3
5x - 4(3 - 2x) / 3 = 19
15x - 12 + 8x = 57
23x = 69, x = 3
y = (3 - 2x) / 3 = (3 - 6) / 3 = -1
ответ: x = 3, y = -1
г) 3x + 2y = 6
5x + 6y = -2
y = (6 - 3x) / 2
5x + 6(6 - 3x) / 2 = -2
5x + 3(6 - 3x) = -2
5x + 18 - 9x = -2
4x = 20, x = 5
y = (6 - 3x) / 2 = (6 - 15) / 2 = -9/2
ответ: x = 5, y = -4,5
объяснение:
Вот накалякал. Разбирайся :)
xy/(x+y) = 5
xz/(x+z) = 7
yz/(y+z) = 9
xy = 5x + 5y
xz = 7x + 7z
yz = 9y + 9z
x(y-5) = 5y
x = 5y/(y-5)
5yz/(y-5) = 35y/(y-5) + 7z
5yz = 35y + 7z * (y-5)
5yz = 35y + 7yz - 35z
2yz + 35y = 35z
y(2z + 35) = 35z
y = 35z/(2z + 35) = z/(2z/35 + 1)
35z^2/(2z + 35) = 315z/(2z + 35) + 9z
35z^2 = 315z + 9z*(2z + 35)
35z^2 = 315z + 18z^2 + 315z
17z^2 = 630z
z=630/17
y = 35*630/(2*630/17 + 35)/17 = 35*630/(1260 + 595) = 22050/1855 = 630 / 53
x = 5*630/(630/53 - 5)/53 = 5*630/((630/53 - 5)*53) = 5*630/365 = 630/73
a9 = 30 - 2(9 -1) = 30 - 16 = 14